2009
DOI: 10.28945/164
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Student Perceptions of their Computer Skills to their Actual Abilities

Abstract: Executive SummaryIn this technology intensive society, most students are required to be proficient in computer skills to compete in today's global job market. These computer skills usually consist of basic to advanced knowledge in word processing, presentation, and spreadsheet applications. In many U.S. states, students are required to demonstrate computer proficiency early in their educational experience by means of passing an assessment test. This research was conducted in North Carolina where all students m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 19 publications
6
51
1
1
Order By: Relevance
“…Elder & Koehn (2009) argue that nursing students rate themselves higher on their skills than their actual performance of computer skills. Similar results are published by Grant et al (2009). Discrepancies between assessed and perceived knowledge and skills may lead to stress and withdrawal of technologies in real settings.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Elder & Koehn (2009) argue that nursing students rate themselves higher on their skills than their actual performance of computer skills. Similar results are published by Grant et al (2009). Discrepancies between assessed and perceived knowledge and skills may lead to stress and withdrawal of technologies in real settings.…”
Section: Introductionsupporting
confidence: 77%
“…Literature findings do not support this result. According to Grant et al (2009) undergraduate university students in North Carolina had a higher perception of their proficiency level than their performance on the assessment for word-processing and spreadsheets. Elder & Koehn (2009) also support the fact that students overrate themselves.…”
mentioning
confidence: 99%
“…Grant, Malloy, & Murphy compared students' CSE ratings with their actual performance on an author-developed computer skills test. Their study demonstrated a gap between what students perceived as their computing skills and their actual assessed skills (Grant, Malloy, & Murphy, 2009). Kilcoyne et al looked at student confidence in the mastery of technology to determine if a student's general confidence in their mastery is representative of their knowledge.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“…However, these studies focused on students' perceived performance of information skills. Following literature from multiple education settings that have stated that students' perceived performance does not necessarily correlate with their measured performance (e.g., Grant, Malloy, & Murphy, 2009;Sarrico, 2010), there is a need to also examine students' measured information skills performance. Lately a few studies have developed instruments to assess measured-performance of information skills among university students in Malaysia (e.g., Abdullah, Ahmad Kassim, Mohd Saad, Tarmuchi, & Aripin, 2006;Edzan, 2007).…”
Section: Statement Of the Problemmentioning
confidence: 99%